Study of Some Hormonal and Biochemical Parameters among Patients with Chronic Liver Diseases - Fingan, Buraq Abdualameer; Al-Warid, Harith Saeed; Al-Sultan, Hayder Jamal (Iraqi Journal of Science, 2024)
It has been revealed previously that chronic liver disease (CLD) may be associated to hormonal fluctuations. The current study, therefore, aimed to evaluate some hormones in CLD patients compared with non-CLD individuals. This case control study was conducted at Gastroenterology and Hepatology Teaching Hospital, Medical city, Baghdad, Iraq during December 2021 to May 2022. One hundred and twenty male patients with CLD (age:14-75 years) and 120 control males (age: 24-70 years) were involved in this study. Serum samples were taken from all individuals and were then analysed for many tests which included hormones (Cortisol, testosterone, prolactin, insulin and thyroid stimulating hormone TSH); biochemical analysis (Prothrombin time PT, international normalized ratio INR and albumin); liver enzymes (aspartate aminotransferase AST, alanine aminotransferase ALT, alkaline phosphatase ALP and gamma glutamyl transferase (GGT)) and interleukins (Interleukin 13 IL-13 and transforming growth factor TGF). Some hormones such as cortisol, prolactin and insulin significantly increased in CLD patients while other hormones (testosterone and TSH) significantly decreased in CLD patients compared with the controls. Results also showed significant increase in liver enzymes among CLD patients. These changes in the hormones and liver enzymes levels may be related with significant increase in INR and albumin which were significantly higher in CLD patients than in the control group. Finally, IL-13 increased significantly in CLD patients while no significant differences were noticed between CLD and control regarding TGF levels. It can, therefore, be concluded that hormonal imbalance can affect people with liver conditions. and that this hormonal imbalance may be associated with high levels of liver enzymes.